Faktor-Faktor Yang Mempengaruhi Perilaku Konsumen Dalam Keputusan Pembelian Makanan Pada Rumah Makan Masakan Padang Di Daerah Boyolali - Iskandar, Umar Zain; , Ir. Irmawati. SE,MSi (2016)
This study aims to determine the factors that influence the behavior of consumers of cultural factors, social factors, personal factors and psychological factors partially and simultaneously on purchasing decisions at restaurant f padang in Boyolali. The population in this study are the customers who visit the restaurant padang in Boyolali. Samples taken as many as 100 respondents using nonprobability Sampling technique with accidental sampling approach. Analysis of the data in this study using validity, reliability test, multiple regression analysis, hypothesis testing (t statistical tests and statistical test F) and Analisia coefficient of determination. The results obtained by analysis of the cultural factor variable t value 2.054 with significance 0.043 <0.05. The results of the analysis of social factors have variable t value of 2.136 with 0.035 significance level of <0.05. The results of the analysis of the personal factor variable have t value of 2.288 with a significance level of 0.024 <0.05. The results of the analysis of the psychological factor variable pick inilai t count equal to 2,682 with significance level of 0.009 <0.05. So that the four factors of positive and significant impact on the decision buying. Value Adjusted R square obtained by 0,361atau 36.1%. Suggestions for restaurants padang is more attention to psychological factors because consumers like the taste of padang food.